Performance enhanced piezoelectric rotational energy harvester using reversed exponentially tapered multi-mode structure for autonomous sensor systems. (3rd February 2023) - Raja, V.; Umapathy, M.; Uma, G.; Usharani, R.
Highlights: RRETMPEH is designed and analytically modeled. The harvester is excited by the beam's gravitational force due to rotation. The harvester uses a non-contact excitation technique to avoid mechanical collisions. Maximum electric power of 247 µW is achieved at the rotating frequency of 9.5 Hz. The harvester could self-power an IoT-based TPMS sensor and thermo-hygrometer. Abstract: Piezoelectric energy harvesting from rotational motion has recently been found to be a promising way to power wireless autonomous sensor systems. In the reported studies, a piezoelectric energy harvester (PEH) structure with a high strain concentration, an inward configuration, and varied rotation axis alignments is shown to play an important role in enhancing the harvester's vibration amplitude and performance. In this paper, a novel rotation-based PEH is proposed to harvest energy from rotational motion using a multi-mode structure (mounted in an inward configuration) consisting of a reversed exponentially tapered beam (primary beam element) and six branched beams (secondary beam elements) attached with a flange to the free end of the primary beam. The beam tip mass axis does not coincide with the rotation axis along its length to improve harvester vibration amplitude. When the harvester spins at a constant speed, the gravitational force acting on the primary and branched beams causes continuous oscillations in the transverse direction. As a result, the primary beam with a piezoelectric patch continually deforms and generates electrical energy. The harvester is theoretically modeled using the Euler-Bernoulli beam theory, and its dynamic equations are derived using the Lagrangian formulation. The proposed harvester is fabricated, and its performance is evaluated through experimentation at a rotating frequency ranging from 1.5–9.5 Hz (90–570 rpm). The harvester offers greater design adaptability in tuning structural parameters to achieve the desired frequencies. An energy management system was designed after investigating the charging behavior of the capacitor with the harvester, and it was found that the proposed harvester was suitable to source wireless autonomous sensor systems. Graphical abstract: Image, graphical abstract